ANALISIS ANTOLOGI PUISI WATHATHITHA KARYA SOSIAWAN LEAK: KAJIAN POSKOLONIAL - Hikmah Kamilah; Septina Azzahwa; Suci Aulia Sya'ban; Purnama Sari; Elmustian (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
This study analyzes Sosiawan Leak's poetry anthology Wathathitha using Homi K. Bhabha's postcolonial theory, particularly the concept of mimicry. This study was conducted to examine how the poems in the anthology represent colonial heritage and neo-feudalism practices that still shape Indonesia's socio-political life. The research method uses a mimetic qualitative approach by repeatedly reading thirteen selected poems and analyzing them through relevant theoretical sources. The results show that Wathathitha presents sharp social criticism of abuse of power, corruption, and bureaucracy that resemble colonial patterns. Mimicry is evident in the emergence of new colonialism and neo-feudalism structures that have been passed down into modern power practices. This anthology confirms that despite formal independence, colonial traces still influence the nation's identity and social system.